2018-2019 China macroeconomic report: China's macroeconomy in the new chapter of reform and opening-up. Issue 3 (3rd July 2019) - Liu, Yuanchun; Liu, Xiaoguang
Abstract: Since 2016, the scenario of stable macroeconomic performance with good momentum has changed due to shifts in global economic architecture, changes in market sentiment, variations in microeconomic bases and mismatched economic policies. Core macroeconomic indicators demonstrated 'continuous slower growth' as downward pressure continued to increase. The situation illustrates that China's macroeconomy has neither stabilised nor entered a steady recovery cycle. A short-term policy may fail to stabilise growth and alleviate the continuous downturn pressure which emerged in 2018. Chinese economy needs comprehensive supply-side structural reforms and opening-up. This report shows that China's internal and external pressures urged wide-range reforms in 2018 and in-depth opening-up in 2019. The year 2019 is crucial for China as it transitions from the dismal 'new normal' phase to a high-quality development mode.